MOTORCYCLE INJURIES: ACCIDENT CHARACTERISTICS AND USE OF PROTECTIVE EQUIPMENT - Ananda Cerqueira Barbosa de Vasconcelos; Tatyanne Silva Rodrigues; Ana Maria Ribeiros dos Santos; Maria Zélia de Araújo Madeira; Elaine Maria Leite Rangel Andrade (Universidade Federal do Paraná, 2019)
Objective: Analyze the relationship among the occurrence of motorcycle injuries, the characteristics of traffic accidents, and use of protective equipment by motorcyclists.Method: This is a correlational cross-sectional study conducted in an urgent care hospital in Teresina, State of Piauí, from December 2016 to April 2017, with 360 injured motorcyclists. Descriptive statistics were analyzed and associations were identified using the chi-square test and Fisher's exact test.Results: Prevalence of injuries was observed in men of low school education level, with own motorcycle, but without a driver license. Also, statistically significant associations were found between the occurrence of head injuries; having a driver license; use of protective equipment; blood alcohol content; lower limb injuries; driving experience; and being economically active. Conclusion: Findings demonstrate the importance of inspection to prevent motorcycle accidents and draw the attention of nursing researchers and professionals who assist this population to the importance of educational actions and campaigns, mainly of nurses in primary care.